PERANCANGAN FASILITAS KERJA PADA PROSES WASHING MATERIAL DI PT. XYZ - zulkifli, Revaldo; Sri Zetli (Computer Science and Industrial Engineering, 2022)
The posture of workers who take positions that are more than normal are consistently very at risk for complaints of Muscoloskeletal Disorders (MSDs). PT.XYZ is engaged in the manufacture of Mechanical, Electrical, and Modular Sub Assy components through various processes using machines. In washing activities, the material that has been processed from the machine is handled manually by workers which is carried out repeatedly every day. In this condition, the body posture is always changing from slouching, slouching, leaning, which is quite a long time which happens more than once every day. Due to non-ergonomic workplace conditions that can endanger the condition of workers in facing risks such as MSDs injury, it is necessary to design work facilities in the material washing process to improve work posture. From the results of the study it was found that the measurement of MSDs complaints using the Nordic Body Map (NBM) questionnaire was not good, where there were complaints experienced by workers above 50%, namely pain in the left shoulder (58.33%) in the right shoulder (56.25%) Pain in the left shoulder. left shoulder. waist (60.41%) on the left calf (58.33%) on the right calf (52.08%) on the left leg (58.33%) on the right leg (58.33%). Calculations using the REBA method have activities with a high risk level for washing 1 activity with a score of 8.5 (high), washing 2 activities with a score of 5.6 (medium) and drying activity with a score of 3 (low). So it is necessary to design ergonomic work facilities to reduce MSDs complaints, namely in the form of a washing table.